White matter hyperintensities induce distal deficits in the connected fibers. Issue 6 (8th January 2021) - Liu, Yanpeng; Xia, Yiwei; Wang, Xiaoxiao; Wang, Yanming; Zhang, Du; Nguchu, Benedictor Alexander; He, Jiajie; Wang, Yi; Yang, Lumeng; Wang, Yiqing; Ying, Yunqing; Liang, Xiaoniu; et al.
Abstract: White matter hyperintensities (WMH) are common in elderly individuals and cause brain network deficits. However, it is still unclear how the global brain network is affected by the focal WMH. We aimed to investigate the diffusion of WMH‐related deficits along the connecting white matters (WM). Brain magnetic resonance imaging data and neuropsychological evaluations of 174 participants (aged 74 ± 5 years) were collected and analyzed. For each participant, WMH lesions were segmented using a deep learning method, and 18 major WM tracts were reconstructed using automated quantitative tractography. The diffusion characteristics of distal WM tracts (with the WMH penumbra excluded) were calculated. Multivariable linear regression analysis was performed. We found that a high burden of tract‐specific WMH was related to worse diffusion characteristics of distal WM tracts in a wide range of WM tracts, including the forceps major (FMA), forceps minor (FMI), anterior thalamic radiation (ATR), cingulum cingulate gyrus (CCG), corticospinal tract (CST), inferior longitudinal fasciculus (ILF), superior longitudinal fasciculus‐parietal (SLFP), superior longitudinal fasciculus‐temporal (SLFT), and uncinate fasciculus (UNC). Furthermore, a higher mean diffusivity (MD) of distal tracts was linked to worse attention and executive function in the FMI, right CCG, left ILF, SLFP, SLFT, and UNC. The effect of WMH on the microstructural integrity of WM tracts may propagate along tracts to distal regions beyond the penumbra and might eventually affect attention and executive function. Abstract : A high burden of tract‐specific WMH was related to an increased MD of distal WM tracts. A higher MD of distal tracts was linked to worse attention and executive function. The microstructural changes caused by WMH may propagate along tracts to distal regions beyond the penumbra.